2018
DOI: 10.1002/nbm.3897
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI in murine radiation‐induced rectocolitis: comparison with histopathological inflammation score

Abstract: Murine radiation-induced rectocolitis is considered to be a relevant animal model of gastrointestinal inflammation. The purpose of our study was to compare quantitative MRI and histopathological features in this gastrointestinal inflammation model. Radiation rectocolitis was induced by localized single-dose radiation (27 Gy) in Sprague-Dawley rats. T -weighted, T -weighted and diffusion-weighted MRI was performed at 7 T in 16 rats between 2 and 4 weeks after irradiation and in 10 control rats. Rats were sacrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Compared to the max ADC spine, mean ADC spine appeared to give better description to disease activity. The ability of ADC in quantifying inflammation has been demonstrated in previous studies 18‐20 and its usage has been validated in axial SpA 9 . In contrast, the currently recommended STIR imaging poorly visualizes intensity of inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…Compared to the max ADC spine, mean ADC spine appeared to give better description to disease activity. The ability of ADC in quantifying inflammation has been demonstrated in previous studies 18‐20 and its usage has been validated in axial SpA 9 . In contrast, the currently recommended STIR imaging poorly visualizes intensity of inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…STIR sequence is highly effective in demonstrating the extent of inflammation, but DWI-ADC allows measurement of intensity. The ability of DWI-ADC in quantifying inflammation intensity has been demonstrated in various diseases 25–27. In previous studies, ADC values were found to correlate with CRP in patients with SpA28 and to be increased in active sacroiliitis 29.…”
Section: Discussionmentioning
confidence: 98%
“…ADC values have been consistently shown to be effective in quantifying the intensity of inflammation in various diseases. [ 23 25 ] In contrast, no association was found with the SPARCC spine MRI score, which used STIR sequence that preferentially measures the extent rather than the intensity of inflammation. Since we only included participants with current back pain, our cohort had higher percentage of MRI inflammation when compared to the international study.…”
Section: Discussionmentioning
confidence: 99%